The state we are in: insights from autopoiesis and complexity theory - Gregory, Amanda (Management Decision, 2006)
Purpose - Following Polanyi, this paper aims to suggest that the Industrial Revolution marked a break-point between pre-industrial society (characterised by integration) and industrial society (characterised by differentiation). Design/methodology/approach - As a conceptual paper, the focus is on drawing out the implications of Luhmann's application of the theory of autopoiesis to industrial society. This discussion leads to critical reflection on the state we are in and the active role we can each play in bringing about change. Findings - Differentiation, without an overall co-ordination and control function within society, has led to the sub-systems (and organisations) becoming self-serving or pathologically autopoietic. Society has a capacity for self-observation, through such mediums as the mass media. Alarm at the apparent increasing rate of change in both social and ecological systems reported by the mass media appears to be drawing us towards a second break-point. The outcome of this revolution, should it come about, is impossible to predict but descent into a new "dark age" is an option as is the re-integration of economic activity with social, religious and political functions. Luhmann's autopoiesis provides a convincing explanation for how society is structured and observing the implications of this. The role of the mass media as an observing system and in bringing information about change to society's attention is emphasised. Practical implications - The paper seeks to provide an explanation for how society is structured and demonstrate how society appears to be passively observing the implications of this. Proposals for both restructuring and the actions we, as active citizens and organisational members, can take to redress our current state are advanced. Originality/value - The paper brings together ideas from a diverse range of fields (including autopoiesis, complexity theory, and systems) and applies them to a highly significant topic.
Business; Systems Studies
Keywords: autopoiesis; complexity theory; economic history; industrial revolution; mass media; social history; social systems

Karl Polanyi: a theorist of mixed economies - Szelényi, Iván; Mihályi, Péter (Theory and Society, 2021)
Karl Polanyi’s scholarship is interpreted in radically different ways. The “hard” reading of Polanyi sees him as a radical socialist; the “soft” reading presents him as a theorist of mixed economy. This article sides with the soft interpretation. It uses Polanyi’s biography to explain his theoretical “elusiveness,” presents a novel interpretation of his three types of economic integration, claiming all economies are “mixed.” While it acknowledges Polanyi as one of the major sources of world system theory, it claims that Polanyi saw not only the dangers, but also the necessity and positive consequences of globalization. Finally, it shows that, in spite of Polanyi’s life-long commitment to the political left, his scholarly work did not offer an apology of socialism. Instead this article uses Polanyi’s theory of economic integration to build a critical political economy of state socialism.
Keywords: capitalism; reciprocity; redistribution; rent-seeking; socialism; world system theory